Synthesis and cytotoxicity of some D-mannose click conjugates with aminobenzoic acid derivatives - Hradilová, Ludmila; Poláková, Monika; Dvořáková, Barbora; Hajdúch, Marián; Petruš, Ladislav (Carbohydrate research, 2012)
Two sets of new conjugates obtained from d-mannose derivatives and o-, m-, and p-substituted benzoic acid esters interconnected through a triazole ring were synthesized by Cu(I) catalyzed azide-alkyne cycloaddition. All synthesized compounds were tested for their in vitro cytotoxic activity against seven cancer cell lines with/without multidrug resistance phenotype as well as non-tumor MRC-5 and BJ fibroblasts. Butyl ester of 4-aminobenzoic acid 6c showed the highest activity among all tested compounds, however, it was active only against K562 myeloid leukemia cells. N-Glycosyltriazole conjugates, both acetylated and nonacetylated at mannose moiety, were almost completely inactive. In contrast, some of the acetylated O-glycosyl conjugates showed cytotoxic activity which was cell line dependent and strongly affected by position of benzoic acid substitution as well as a length of its ester alkyl chain; the most potent compound was acetylated mannoside conjugated with octyl ester of m-substituted benzoic acid. However, deacetylation resulting in hydrophilicity increase of the glycosides almost completely abolished their cytotoxic potency.
Keywords: Mannose; stereoizomerie; Drug Evaluation, Preclinical; Humans; preklinické hodnocení léčiv; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Aminobenzoates; mannosa; Dose-Response Relationship, Drug; Antineoplastic Agents; Click Chemistry; click chemie; lidé; proliferace buněk; molekulární struktura; Stereoisomerism; Molecular Structure; buněčné linie; Cell Line; aminobenzoáty; Cell Proliferation; protinádorové látky; vztah mezi dávkou a účinkem léčiva; fibroblasty; Fibroblasts